Sinergi Kampus dan Dunia Usaha dalam Meningkatkan Kompetensi Mahasiswa melalui Pelatihan Dasar Manajerial Proyek - Galib, Mukhtar; Gunawan, Aden; Maulana, Maulana; Syam, Jumiati (ABDI DAYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The basic project managerial training program was designed to equip students with technical and non-technical skills for managing simple projects. The program involved 20 participants over four days, encompassing theoretical learning, simulations, and a field visit to PT. Tuju Wali Wali’s project site. Participants were trained to use planning tools such as Gantt charts and SWOT analysis, as well as to understand basic budget management. Additionally, communication, teamwork, and conflict management skills were developed through case-based simulations. The field visit provided practical insights into real project challenges and management strategies. Evaluation results indicated that participants could understand and apply basic managerial concepts, offer innovative input for local needs, and gain experience relevant to the workforce. With its experiential learning approach, this training successfully bridged academic theory and practical application, fostering synergy between universities, businesses, and communities